2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE) 2014
DOI: 10.1109/tale.2014.7062581
|View full text |Cite
|
Sign up to set email alerts
|

Does gender matter for collaborative learning?

Abstract: In our recent work we have proven quantitatively that collaborative learning improves students' knowledge retention and boosts the quality of attained learning outcomes. In this research we investigate the role that the students' gender plays in their engagement during collaborative learning and their learning performance as assessed by the teacher. In the context of the EBTIC developed Collaborative Learning Environment deployed at Khalifa University along the sequence of three group courseworks over one seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Also, in this setting, females paid more attention but showed less relevance and satisfaction towards the course than male students. Again, the socio-cultural context affected differentially female and male students' attitudes towards biology, supporting previous studies that posed the necessity to implement context-based learning environments for each gender within conservative societies (Almasri Firas et al, 2021;Brownell et al, 2013;Cen et al, 2014;Colbeck et al, 2001).…”
Section: Attitude and Achievement Towards Biology Based On Students' ...supporting
confidence: 79%
See 1 more Smart Citation
“…Also, in this setting, females paid more attention but showed less relevance and satisfaction towards the course than male students. Again, the socio-cultural context affected differentially female and male students' attitudes towards biology, supporting previous studies that posed the necessity to implement context-based learning environments for each gender within conservative societies (Almasri Firas et al, 2021;Brownell et al, 2013;Cen et al, 2014;Colbeck et al, 2001).…”
Section: Attitude and Achievement Towards Biology Based On Students' ...supporting
confidence: 79%
“…Female students are more committed to university life; they spend more time preparing for classes, studying, and reading (Grebennikov & Skaines, 2009) and prefer collaborative learning more than male students (Lundeberg & Moch, 1995;Opdecam et al, 2014;Stump, Hilpert, et al, 2011). Gender plays a role in collaborative classroom learning settings because students need to interact face-to-face, affecting their attitudes and achievements in science courses (Cen et al, 2014;Chennabathni & Rejskind, 1998;Colbeck et al, 2001;Opdecam et al, 2014;Stump, Hilpert, et al, 2011). The effect of gender-grouping was observed in many western countries, including the U.S. (Gnesdilow et al, 2013b;Guo et al, 2018;Myaskovsky et al, 2005;Sormunen-Jones et al, 2000;Xie et al, 2015b), the U.K. (Carli, 2001;Milliken & Martins, 1996;Takeda & Homberg, 2014), and the Netherlands (Harskamp et al, 2008).…”
Section: Impact Of Gender and Gender-grouping In-classroommentioning
confidence: 99%
“…Previous research has also showed that single-gender collaborative groups work to the advantage of female students who seem to be more willing to share and cooperate with each other when faced with unfamiliar tasks [30]. Despite this, other research in the UAE context found that students in mixed-gender groups accomplished the task more successfully and achieved better academic results than did the same-gender groups [31]. This likely stemmed from "the synergies and efficiencies of interactive learning in a diverse group of students" [31, p. 433].…”
Section: Discussionmentioning
confidence: 99%
“…Balanced-gender heterogeneous groups and homogeneous female groups tend to (i) outperform the others (Zhan et al, 2015;Cen et al, 2014).…”
Section: Visual Analysis Using Cnomentioning
confidence: 99%
“…tributions (Cen et al, 2014). Some individual aspects, such as depressive symptoms and self-esteem, are differentially stratified by gender (Pachucki et al, 2015) and thus should be carefully observed by the teacher as they also affect individual and group performances.…”
Section: Visual Analysis Using Cnomentioning
confidence: 99%